Professional propaedeutic council in the university - N. N. Malyarchuk; G. M. Krinitzyna; E. V. Pashchenko; V. V. Pivnenko (Russian State Vocational Pedagogical University, 2019)
Introduction. The implementation of inclusive education (IE) for people with disabilities in Russian Federation is enshrined in legal acts. The state sets the task of implementing new requirements to provision of education for people with disabilities in health care in higher education. However, one of the obstacles to IE is the lack of readiness for new requirements and inclusive activity of a vast majority of teachers. When developing and implementing adapted vocational education programmes (AVEP) for students with disabilities, the teachers need regular consultations and specialists' qualified assistance in the sphere of medicine, defectology, pedagogical and correctional psychology.The aim of the present publication was to justify the rationale for creating a professional propaedeutic council (PPC) at a higher educational institution as a permanent system to manage and support the process of vocational education for people with disabilities.Methodology and research methods. The methodological basis of the study involved inclusive and propaedeutic approaches to education and the principles of multi-, inter-, trans- and cross-disciplinary. In the course of the research, a complex of theoretical and empirical research methods was employed: analysis, synthesis, moving from abstract to concrete, systematisation, and generalisation.Results and scientific novelty. Today, different levels of government have declared the need for providing professional working capacity of people with disabilities in order to become socially and financially independent and avoid social dependence; at the higher vocational school, there is a change vector for social policy concerning this category of citizens - from delivery of educational services to reorientation to their socialisation. As a state strategy in higher education, vocational education should be provided for everyone creating equal opportunities. At some large universities, structural divisions are already functioning (resource centers including the defectology faculties and departments), which promote satisfaction of special educational needs of students with disabilities. Meanwhile, numerous studies point the fact that teachers are not ready to work with students, who have visual, hearing and musculoskeletal disorders. Higher educational institutions, which are just starting inclusive education without internal resources for such activity, are offered to organise PPCs. PPCs should involve the experts, who carry out medical, psychological and pedagogical support for students with disabilities and provide comprehensive assistance to teachers in addressing the particular issues of inclusive education.The article reveals the mission, purpose and tasks of PPC in university. The structure of such council, its organisational-network, medical-social and educational-methodological blocks are presented. Functional duties of experts and specialists, united in each of PPC blocks, are defined.Practical significance. The principles of PPC work and the offered structure of AVEP, taking into account the clinical diagnosis and physical disabilities of students, can be taken as the basis of realisation of inclusive education at university.